(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article investigates the influence of international trade on the logistics strategies of Fiat Automobiles, one of the leading automakers in the global automotive sector. With a significant presence in several markets, Fiat faces challenges and opportunities that shape its vehicle and parts sales operations. The research, based on a case study, analyzes the intersection between logistics and international trade, exploring how Fiat adapts its logistics practices to meet global demand. The theoretical framework addresses fundamental concepts of international logistics, including planning and execution of global supply chains, and discusses theories of trade, such as Ricardo’s comparative advantages and Grubel and Lloyd’s intra-industry trade. The survey highlights emerging trends, such as the digitalization of logistics processes and the growing importance of sustainability, as well as challenges such as tariff barriers, currency fluctuations, and the need for compliance with international regulations. The results of the analysis demonstrate that Fiat adopts an integrated logistics approach, combining advanced technologies and strategic partnerships to optimize the transportation and distribution of vehicles and parts. The company uses supplier tracking and management systems, which contributes to reducing costs and improving operational efficiency. The research concludes that the ability to adapt and innovate in logistics strategies is crucial for Fiat’s competitiveness in the global market. Recommendations are presented for future practices, emphasizing the importance of investments in technology and the formation of strategic alliances, in addition to the adoption of sustainable practices, to face the challenges of international trade effectively.